Redefining Work -Integrated Learning in Universities of Technology - Bohloko, GM (South African Journal of Higher Education, 2016)
This article makes a case firstly, for Work Integrated Learning (WIL) as an integral part of the curriculum in universities of technology and secondly, as a pedagogical issue. I argue that, WIL represents the re-contextualised aspects of specialised knowledge in curricula of the various professions and that WIL should equally draw knowledge from disciplines. WIL is an example of re-contextualising conceptual knowledge into procedural knowledge at the workplace. I argue further that WIL tends to be better integrated with curricula and qualifications in the old professions that are strongly regulated by a variety of accreditations by boards and councils, who oversee both the formal curricula and competence levels of graduates. The article proposes the notion of conceptual and contextual approaches to understand WIL in a university of technology. Consequently, the development of an approach to a WIL component of the curriculum that transcends specific contexts and ensures the durability of offerings is proposed. Key words: conceptual and contextual knowledge, re-contextualisation, work integrated learning, specialised knowledge, accreditation